Pulmonary Hypoplasia Induced by Oligohydramnios: Findings from Animal Models and a Population-Based Study - Chun-Shan Wu; Chung-Ming Chen; Hsiu-Chu Chou (Pediatrics and Neonatology)
Pulmonary hypoplasia is a substantial cause of death in newborn infants, and oligohydramnios is one of the most commonly associated abnormalities. Lung growth is influenced by physical factors such as the intrauterine space, lung liquid volume and pressure, and fetal breathing movements. During lung development, the main physical force experienced by the lungs is stretching induced by breathing movements and the lung fluid in the airspaces. Oligohydramnios reduces the intrathoracic cavity size, thus disrupting fetal lung growth and leading to pulmonary hypoplasia. The exact mechanism by which oligohydramnios alters the respiratory system structure and the effect of oligohydramnios on long-term respiratory outcomes remain unknown. In this review, we summarize the effects of oligohydramnios on lung development, discuss the mechanisms of oligohydramnios-induced pulmonary hypoplasia identified in various animal studies, and describe the long-term respiratory outcomes in childhood of oligohydramnios-exposed fetuses reported by a population-based study.